In vitro and in vivo characterization of erythrosin B and derivatives against Zika virus - Zhong Li; Jimin Xu; Yuekun Lang; Xiangmeng Wu; Saiyang Hu; Subodh Kumar Samrat; Anil M. Tharappel; Lili Kuo; David Butler; Yongcheng Song; Qing-Yu Zhang; Jia Zhou; et al. (Elsevier, 2022)
Zika virus (ZIKV) causes significant human diseases without specific therapy. Previously we found erythrosin B, an FDA-approved food additive, inhibited viral NS2B−NS3 interactions, leading to inhibition of ZIKV infection in cell culture. In this study, we performed pharmacokinetic and in vivo studies to demonstrate the efficacy of erythrosin B against ZIKV in 3D mini-brain organoid and mouse models. Our results showed that erythrosin B is very effective in abolishing ZIKV replication in the 3D organoid model. Although pharmacokinetics studies indicated that erythrosin B had a low absorption profile, mice challenged by a lethal dose of ZIKV showed a significantly improved survival rate upon oral administration of erythrosin B, compared to vehicle control. Limited structure−activity relationship studies indicated that most analogs of erythrosin B with modifications on the xanthene ring led to loss or reduction of inhibitory activities towards viral NS2B−NS3 interactions, protease activity and antiviral efficacy. In contrast, introducing chlorine substitutions on the isobenzofuran ring led to slightly increased activities, suggesting that the isobenzofuran ring is well tolerated for modifications. Cytotoxicity studies indicated that all derivatives are nontoxic to human cells. Overall, our studies demonstrated erythrosin B is an effective antiviral against ZIKV both in vitro and in vivo.